2015
DOI: 10.5482/hamo-14-09-0044
|View full text |Cite
|
Sign up to set email alerts
|

The platelet P2 receptors in inflammation

Abstract: SummaryIn addition to their well characterized and established role in haemostasis and thrombosis, platelets contribute to the pathogenesis of inflammation. Adenine nucleotides are signalling molecules that regulate the function of virtually every cell in the body, by interacting with P2 receptors. Their important role in inflammation is well established. In the last few years, the pro-inflammatory roles of adenine nucleotides interacting with their platelet P2 receptors has emerged. In particular, it was show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 76 publications
0
14
0
2
Order By: Relevance
“…Additional evidence for a role of the platelet P2Y 12 receptor in human asthma was provided by recent clinical observations that P2Y 12 receptor variants were associated with altered lung function in a large familybased asthma cohort and that prasugrel tended to decrease the bronchial hyper-reactivity to mannitol in patients with allergic asthma in a randomized placebo-controlled trial. 35 In sharp contrast, a recent study reported no involvement of P2Y 12 in allergic inflammation in ovalbumin-challenged mice, whereas the platelet P2Y 1 receptor appeared to be pivotal (see below). 44 Obviously, there are conflicting data concerning the part played by the P2Y 12 receptor in asthma, and whether the discrepancies might be related to differences in the mouse models of allergic inflammation or to the use of P2Y 12 receptor antagonists versus P2Y 12 −/− mice will require further investigation.…”
Section: 41mentioning
confidence: 72%
See 1 more Smart Citation
“…Additional evidence for a role of the platelet P2Y 12 receptor in human asthma was provided by recent clinical observations that P2Y 12 receptor variants were associated with altered lung function in a large familybased asthma cohort and that prasugrel tended to decrease the bronchial hyper-reactivity to mannitol in patients with allergic asthma in a randomized placebo-controlled trial. 35 In sharp contrast, a recent study reported no involvement of P2Y 12 in allergic inflammation in ovalbumin-challenged mice, whereas the platelet P2Y 1 receptor appeared to be pivotal (see below). 44 Obviously, there are conflicting data concerning the part played by the P2Y 12 receptor in asthma, and whether the discrepancies might be related to differences in the mouse models of allergic inflammation or to the use of P2Y 12 receptor antagonists versus P2Y 12 −/− mice will require further investigation.…”
Section: 41mentioning
confidence: 72%
“…6,35,36 In addition, the P2Y 12 receptor expressed on VSMCs has been reported to promote proinflammatory and mitogenic responses through a thrombin-induced pathway in vitro. 37 All these findings point to a potential contribution of this receptor to inflammatory diseases.…”
Section: P2y 12 Receptor In Inflammationmentioning
confidence: 99%
“…Evidence has also emerged for a role to the platelet P2Y 12 R in the pathogenesis of allergic bronchial asthma [59]. Cysteinyl leukotrienes (LTs) LTC 4 , LTD 4 and LTE 4 are biologically active lipids that play a role in allergic asthma [60].…”
Section: Role Of P2y 12 R In Platelet Responses To Agonists Other Thamentioning
confidence: 99%
“…ATP and P2X3R have a long history of involvement with pain and inflammation [21,22]. In colitis, more internal ATP was produced and expression of P2X3R at the end of colorectal nerves was also increased, thus leading to hypersensitivity of rectocolon [23][24][25].…”
Section: Introductionmentioning
confidence: 99%